Design of a multiparameter data acquisition and control system for in situ seabed observation base stations - Chao Zhong; Jing'an Lu; Dongju Kang; Qianyong Liang (IET Science, Measurement & Technology, 2024)
Abstract With the exploration, development, and research of deep‐sea resources, there is an urgent need for long‐term and continuous observation data of the deep‐sea seabed boundary layer. The traditional method of deep‐sea seabed survey and sampling based on scientific research vessels has the discontinuity of observation data in space and time scales. There are some problems in the seabed in situ observation method based on the seabed observation network for low mobility and high operation and maintenance costs, restricting the in‐depth understanding of the dynamic change process of the deep‐sea floor. To solve the above problems, an open and modular data acquisition control system was designed based on an embedded system and signal processing technology. In terms of the physical, chemical, geological, and ecosystem characteristics of the seafloor or near the seafloor boundary layer, various functional sensors and instrumentation were matched to form an independent underwater integrated measurement or experimental device, eventually realizing in situ multiparameter and long‐time series observations of the seafloor. The system data acquisition and control test were completed through laboratory experiments, which verified the feasibility of the system design. The research showed important theoretical and technical reference significance for the exploration and development of resources in the submarine boundary layer and the promotion of deep‐sea scientific research.